A cruel deception [compact disc, unabridged] - Todd, Charles (Todd, Charles. Bess Crawford mystery., 2019)
The Armistice of November 1918 ended the fighting, but the Great War will not be over until a Peace Treaty is drawn up and signed by all parties. Representatives from the Allies are gathering in Paris, and already ominous signs of disagreement have appeared. Sister Bess Crawford is asked to carry out a personal mission in Paris for a Matron at the London headquarters of The Queen Alexandra's. Bess is facing decisions about her own future, even as she searches for the man she is charged with helping. When she does locate Lawrence Minton, she finds a bitter and disturbed officer who has walked away from his duties at the Peace Conference and is well on his way toward an addiction to opiates. When she confronts him with the dangers of using laudanum, he tells her that he doesn't care if he lives or dies, as long as he can find oblivion. What is driving this man to a despair so profound it can only end with death? To prevent a tragedy, she must get at the truth as quickly as possible.